A novel study on the sandwich-structure strain sensor using ethylene-vinyl acetate-based hot-melt adhesive mesh web: Fabrication, properties, and modeling - Qu, Muchao; Fang, Jiaqiang; Mu, Chenzhong; Li, Yanfeng; Huang, Shaojuan; Han, Lei; Hiemer, Stefan; Xu, Wei; Qin, Yijing (Journal of Applied Polymer Science, 2022)
In this study, a flexible strain sensor consisting of carbon nanotubes (CNTs) and ethylene-vinyl acetate (EVA)-based hot-melt adhesive web (HAW) is proposed with the advantages of low cost and easy fabrication. Six different weight fractions of the CNTs were employed in producing the three-layer sandwich-structure composite membrane. The morphology and internal particle structure of the cross section of the EVA/CNTs composite membranes was studied using scanning electron microscopy. The mechanical properties as well as the mechanical-electrical behavior of the EVA/CNTs sensors were investigated, showing a gauge factor up to 477. In addition, two mathematical equations to establish the relationship between the output electrical signal and the input strain signal during the monotonic and cyclic measurements were proposed, respectively. Overall, this study provides a solvent-free one-step approach for the preparation of flexible strain sensors with innovative and broad application prospects, and offers some insight into the mathematical prediction of the strain sensing behavior.
CRIS-Team WoS Importer:2022-10-21